Role of Phosphorylated Gonadotropin-Regulated Testicular RNA Helicase (GRTH/DDX25) in the Regulation of Germ Cell Specific mRNAs in Chromatoid Bodies During Spermatogenesis - Anbazhagan, Rajakumar; Kavarthapu, Raghuveer; Coon, Steven L.; Dufau, Maria L. (Frontiers in Cell and Developmental Biology, 2020)
GRTH/DDX 25 is a member of the DEAD-box family of RNA helicases that play an essential role in spermatogenesis. GRTH knock-in (KI) mice with the human mutant GRTH gene (R242H), show loss of the phospho-species from cytoplasm and chromatoid bodies (CB) with preservation of the non-phospho form in the cytoplasm, Nucleus and CBs. GRTH KI mice are sterile, lack elongated spermatids and spermatozoa with spermatogenic arrest at step 8 of round spermatids which contain CB markedly reduced in size. We observed an absence of phospho-GRTH in CB of GRTH KI mice. RNA-Seq analysis of mRNA isolated from CB revealed 1421 genes show differential abundance of which 947 genes showed decrease in abundance and 474 genes showed increase in abundance in GRTH KI mice. The transcripts related to spermatid development, differentiation and chromatin remodeling (Tnp1/2, Prm1/2/3, Spem1/2, Tssk 2/3/6, Grth, tAce and Upf2) were reduced, and transcripts encoding for factors involved in RNA transport, regulation and surveillance, transcriptional and translational regulation (Eef1a1, Ppp1cc, Pabpc1, Ybx3, Tent5b, H2al1m, Dctn2 and Dync1h1) were increased in the CB of KI mice and were further validated by qPCR. In round spermatids of wild type mice mRNAs of Tnp2, Prm2 and Grth were abundantly co-localized with MVH protein in the CB while in GRTH KI mice were minimally present. In addition, GRTH binding to Tnp1/2, Prm1/2, Grth and Tssk6 mRNAs was found to be markedly decreased in KI. These results demonstrate the importance of phospho-GRTH in the maintenance of structure of the CB and its role in storage and stability of germ cell specific mRNAs during spermiogenesis.